Flame retardants for textile materials - Choudhury, Asim Kumar Roy (Boca Raton, FL : CRC Press, 2020)
"This book focuses on flame retardants (FR) for textile materials. It discusses basics of flame retardancy and flammability and covers various types of flame retardants and materials, including natural FRs, halogen-, phosphorous-, and nanomaterial-based FRs. It also covers methods of applications of FRs and discusses FRs and the environment. Aimed at the practioner and textile engineering professional this work aims to ensure development of safe textile materials for various uses, including apparel, protective wear, floor coverings, upholstery, drapery, and others"--
OCLC-licensed vendor bibliographic record.
Keywords: Fireproofing of fabrics; Fire resistant materials; TECHNOLOGY / Material Science; TECHNOLOGY / Textiles & Polymers